Lif tipinin ve polietilen filmin ultrasonik yöntemle birleştirilmiş çok katmanlı nonwoven kumaşların mekanik özellikleri üzerine etkisi - (:unkn) unknown (My University, 2014)
Bu çalışmada ultrasonik yöntemle birleştirilmiş nonwoven kumaşların mekanik özellikleri incelenmiştir. Bu amaçla 3 farklı gramajda polipropilen, poliester ve poliester viskon nonwoven kumaş kullanılmıştır. Ardından nonwoven kumaşlar birbirleriyle ultrasonik dikiş makinesiyle birleştirilmiş ve 2 katmanlı yapılar üretilmiştir. Ayrıca iki nonwoven kumaş arasına polietilen film yerleştirilerek bu 3 yüzey ultrasonik dikiş makinesiyle birleştirilmiş ve 3 katmanlı yapılar üretilmiştir. 2 ve 3 katlı yapıların kopma dayanımı ve kopma anındaki uzama özellikleri araştırılmıştır ve polietilen filmin 3 katmanlı yapıların mekanik özelliklerine etkisi incelenmiştir. En yüksek mekanik özellikler 3 katmanlı polipropilen polietilen film polipropilen yapısında elde edilmiştir.

In this study mechanical properties of the ultrasonically bonded nonwoven fabrics were investigated. For this purpose polypropylene, polyester and polyester-viscose nonwoven fabrics which have three different fabric area densities were obtained. Then nonwoven fabrics were bonded to each other by using ultrasonic sewing machine and two layered structures were produced. Also polyethylene film was placed between two nonwoven fabrics and these three surfaces were bonded by using ultrasonic sewing machine and three layers fabrics were obtained. Tensile strength and elongation at break properties of the 2 and 3 layers structures were investigated and effect of the polyethylene film on the mechanical properties of the 3 layers structures was studied. And higher mechanical properties were obtained from the 3 layers polypropylene-polyethylene film-polypropylene structures.
Effect of fiber type and polyethylene film on mechanical properties of ultrasonically bonded multi layer nonwoven fabrics
Keywords: Malzeme Bilimleri, Tekstil